(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The use of plant extracts as insecticidal plants has become widespread as alternative to synthetic insecticides and their alternative use as growth stimulants and nutritional enhancer should be evaluated. Therefore, this experiment was conducted to determine the effects of Fiscus exasperata leaf, and the combination of both extracts on the Amaranthus hybridus growth, proximate and mineral contents in the harvested leaves. The experiment was arranged in randomized complete block design and each treatment was replicated three times. Data were collected on plant height, number of leaves, yield, proximate and mineral contents of the harvested leaves. Data collected were subjected to statistical analysis and means were separated using Ducan’s multiple range test. The results showed that plant height, number of leaves and yield obtained from the amaranth plants treated with F. exasperata extracts were comparable with that of Chlorpyrifos. However, harvested leaves from amaranth plants treated with F. exasperata extracts had higher mineral and proximate contents than harvested leaves from plants sprayed with Chlorpyrifos and plant extracts. Meanwhile, F. exasperata leaf improved nutritional contents of the harvested leaf than F. exasperate bark extracts and the treatment combinations performed better than the mixture of F. exasperata leaf and back extract with respect to nutritional contents but none of the plant extract formulations caused negative effects on the plant growth. Therefore, F. exasperata extract can be used a major source of green vegetable plant growth and nutritional enhancer.